Load of Aeromonas salmonicida in Swamp Water and its Pathogenicity to Koi, Anabas testudineus (Bloch) - Afza, Rowshatul; Hussain, M Afzal; Khatun, Habiba; Yeasmin, Sabina; Hossain, Md Iqbal; Rahman, M Habibur (Journal of Bio-Science, 2009)
Among the fishery resources, swamps are very important for various fish species such as Oreochromis nilotica, Oreochromis mossambica, Anabas testudineus, Channa punctatus and Heteropneustes fossilis. Swamps require shorter time and small investment for fish culture (Rahman et al. 1998). However, diseases are major problems in fish production both in culture system and wild condition in Bangladesh (Rahman and Chowdhury 1996). Bacteria, especially Aeromonas sp. is one of the causative agents of fish diseases. Bangladesh is situated in the tropical zone. Temperature is one of the important factors which affect the growth of pathogenic bacteria (Ljungh and Wadstrom 1982). Aeromonas sobria increases and grows at 17- 25Â°C (Rahman and Chowdhury 1996). Aeromonas sp. is the causative agent of various kinds of ulcerative disease of fishes (Karunasagar and Sugumar 1995). Yesmin et al. (2004) and Chowdhury and Baqui (1997) reported that Aeromonas is a very common pathogen in carps and live fishes. Hossain et al. (2006) worked on the bacterial load, Pseudomonas aeruginosa and their artificial infection to Oreochromis niloticus. The present study was undertaken to investigate the bacterial load in swamp water and the pathogenicity of A. sobria in A. testudineus. Â  doi: 10.3329/jbs.v15i0.2162 J. bio-sci. 15: 181-184, 2007